O Desenvolvimento sustentável de regiões semiáridas do Brasil e dos Estados Unidos: o papel do Departamento Nacional de Obras Contra as Secas (DNOCS) e do United States Bureau of Reclamation (USBR) - Araújo, Maria Zita Timbó (2013)
The Departamento Nacional de Obras Contra as Secas - DNOCS is a secular institution of the Brazilian Federal Government, created in 1909 and acting in nine states of the Semi-arid Northeast, with the purpose of sustainably implementing the regional development of the more encompassing National Water Resources Policy. The UNITED STATES BUREAU OF RECLAMATION - USBR is, also, a secular institution, founded in 1902, which acts in seventeen states of the dry American West, whose mission is to “manage, develop, and protect water and related resources in an environmentally and economically sound manner in the interest of the American public.” This work consists in researching and learning about practical experiences, projects elaborations, construction works, water management and regional development of those two important institutions. Taking into account the knowledge of the inflexion moment in which the USBR changed its performance, adapting it to today’s West-American Water Resources Management, and considering paradigm shifts relative to the environment and safety of water facilities, this study constitutes a technical and scientific contribution to decision-making in the formulation of a Project for Institutional Restoration of DNOCS, that enhances the management of water resources in the semi-arid Brazilian northeastern region.